2010
DOI: 10.1001/archinternmed.2010.447
|View full text |Cite
|
Sign up to set email alerts
|

Tamsulosin Hydrochloride vs Placebo for Management of Distal Ureteral Stones

Abstract: clinicaltrials.gov Identifier: NCT00151567.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
3
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
1
38
3
4
Order By: Relevance
“…Sebastein V et al studied that out of total 129 patients, at inclusion, mean (SD) stone diameters were 3.2 (1.2) and 2.9 (1.0) mm in the placebo and tamsulosin groups. 17 In present study in group A only 12 (24%) patients experienced pain relapses whereas in group B 32 (64%) patients reported pain relapses. In group A 38 (76%) patients experienced no episode of relapse of pain whereas only 18 (36%) patients were pain free in group B.…”
Section: Discussioncontrasting
confidence: 47%
“…Sebastein V et al studied that out of total 129 patients, at inclusion, mean (SD) stone diameters were 3.2 (1.2) and 2.9 (1.0) mm in the placebo and tamsulosin groups. 17 In present study in group A only 12 (24%) patients experienced pain relapses whereas in group B 32 (64%) patients reported pain relapses. In group A 38 (76%) patients experienced no episode of relapse of pain whereas only 18 (36%) patients were pain free in group B.…”
Section: Discussioncontrasting
confidence: 47%
“…Among the 8 placebo-controlled, double-blinded, randomized trials of tamsulosin in patients with ureteral stones, only 1 included ureteral stones of all locations, 8 whereas the remaining studies included distal ureteral stones identified by CT or kidney, ureter, and bladder radiographs. Four studies were conducted in an emergency department (ED) setting, 8,9,19,23 and 4 were conducted in urology clinics in a number of different countries, 17,18,21,24 including Australia, Egypt, France, India, Qatar, Switzerland, the United Kingdom, and the United States.…”
Section: Resultsmentioning
confidence: 99%
“…Six trials provided tamsulosin for 28 days, 1 provided the drug for 21 days, 21 and the remaining study provided tamsulosin for 42 days. 23 The control group in each study received a placebo pill.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations